NON-ENGLISH MAJOR STUDENTS’ INSIGHTS ON TEACHER SUPPORT IN EFL CLASSROOMS - Mudra, Heri (ELTR Journal, 2025)
Teacher support (henceforth TS) in EFL classrooms emerges as psychological empowerment for non-English major students (henceforth NEMS), even though not all EFL teachers are aware of such communicative interaction. Grounded on the rationale, this current study investigated how the EFL teachers contributed to the English skill development of students who did not engage with English majors. A total of 279 students from various majors voluntarily participated in an online survey, ensuring that they selected appropriate perceptions. The findings disclosed that the EFL teachers had both positive and negative contributions towards NEMS English learning experiences. However, such imbalanced supports seemed to be randomly performed by different teachers in different contexts, meaning that similar EFL teachers treated students’ English learning differently when they were influenced by other factors, such as students’ difficulty level or teacher competence. In short, it is believed that TS leads to NEMS positive attitude and understanding towards English skills. A recommendation is highly expected to configure how every EFL teacher determines academic or social support for all NEMS in the current and future EFL classrooms.